Pengaruh Disiplin dan Kompetensi Kerja Terhadap Kinerja Karyawan pada PT. Cardig Anugrah Sarana Catering - Nur Fitriana Azizi; Cecep Haryoto (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
The purpose of this study was to determine the effect of Work Discipline and Work Competence on Employee Performance at PT. Cahaya Anugrah Sarana Catering. This study used observation and questionnaires as instruments. Fifty employees were selected as respondents, using a saturated sampling technique. The research approach used was quantitative associative analysis using primary data. Data analysis utilized SPSS software with multiple linear regression analysis. The results showed that partially, Work Discipline had no significant effect on Employee Performance with a significance value >0.05. Meanwhile, Work Competence had a positive and significant effect on Employee Performance with a significance value <0.05. Simultaneously, Work Discipline and Work Competence had a positive and significant effect on Employee Performance at PT. Cahaya Anugrah Sarana Catering. These findings indicate that improving employee performance in a company is more influenced by the level of employee work competence, such as knowledge, skills, and abilities, than by work discipline alone. Therefore, companies need to focus more on efforts to improve employee competence through continuous training and development.